2009
DOI: 10.1097/aap.0b013e3181ae7323
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Location of the Radial Nerve Confirmed by Nerve Stimulation During Axillary Brachial Plexus Blockade

Abstract: : The radial nerve uncommonly lies immediately deep to the axillary artery. It is frequently located on the caudad side of the artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The higher volume required to surround the radial nerve probably reflects the relative difficulty of identifying this nerve in the axilla and ensuring that it was surrounded with anaesthetic. It may have been helpful to use nerve stimulation when performing the blocks for this reason, as suggested for the radial nerve by Wong and colleagues 14 recently. In contrast, the musculocutaneous nerve tended to be surrounded with a relatively low volume, probably explained by its location between the two fascial planes of biceps and coracobrachialis.…”
Section: Discussionmentioning
confidence: 99%
“…The higher volume required to surround the radial nerve probably reflects the relative difficulty of identifying this nerve in the axilla and ensuring that it was surrounded with anaesthetic. It may have been helpful to use nerve stimulation when performing the blocks for this reason, as suggested for the radial nerve by Wong and colleagues 14 recently. In contrast, the musculocutaneous nerve tended to be surrounded with a relatively low volume, probably explained by its location between the two fascial planes of biceps and coracobrachialis.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound anatomy and the disposition of nerves in the axillary fossa have been investigated both clinically and anatomically to elucidate the nerve–vessel relationship. Gili et al () described the pattern of distribution of nerves around the brachial artery as assessed by ultrasound scanning and neurostimulation during the plexus blockade: the position of the radial nerve is at four or five o'clock in most cases, though there are variations, and the radial nerve is more difficult to visualize than other nerves (Wong et al, ; Silva et al, ). The recognition and disposition of the radial nerve are matters of interest for the clinician, who has to decide whether to direct the needle just above or below the artery to reach it.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the time to onset of sensory block was 17.0 ± 10.4 mins and the duration of the block was 86.0 ± 42.9 mins with 7.5 ml of bupivacaine 0.5%. In another study, it has been reported that as the LA volume was decreased, so the duration of the block decreased and this shows that blocks applied with low volumes of LA could be selected for day-patient surgical interventions [ 20 ]. However, it should be kept in mind that the onset of a block is prolonged in these applications as it could be a disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…In the reduction of a volume that will be able to provide a block, visualization and location of the radial nerve are difficult and seems to be a restriction of the blockage. It has been proposed that differentiation of the site of the radial nerve with a nerve stimulator could be useful in decreasing the LA volume to be administered [ 20 ]. In the current study, it was determined that the use of USG guidance alone could be useful in this issue compared to conventional methods.…”
Section: Discussionmentioning
confidence: 99%